Answer:
![y=\frac{\sqrt{x-1} }{4}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B%5Csqrt%7Bx-1%7D%20%7D%7B4%7D)
Step-by-step explanation:
The given equation is
![y=16x^2+1](https://tex.z-dn.net/?f=y%3D16x%5E2%2B1)
For this function to have an inverse, we must restrict the domain, say ![x\ge0](https://tex.z-dn.net/?f=x%5Cge0)
We interchange x and y to get,
![x=16y^2+1](https://tex.z-dn.net/?f=x%3D16y%5E2%2B1)
We now make y the subject to get;
![x-1=16y^2](https://tex.z-dn.net/?f=x-1%3D16y%5E2)
![x-1=16y^2](https://tex.z-dn.net/?f=x-1%3D16y%5E2)
We divide through by 16 to get;
![\frac{x-1}{16}=y^2](https://tex.z-dn.net/?f=%5Cfrac%7Bx-1%7D%7B16%7D%3Dy%5E2)
We now take the square root of both sides to get;
![\pm \sqrt{\frac{x-1}{16}}=y](https://tex.z-dn.net/?f=%5Cpm%20%5Csqrt%7B%5Cfrac%7Bx-1%7D%7B16%7D%7D%3Dy)
![y=\pm \frac{\sqrt{x-1} }{4}](https://tex.z-dn.net/?f=y%3D%5Cpm%20%5Cfrac%7B%5Csqrt%7Bx-1%7D%20%7D%7B4%7D)
Since
, the inverse function is
![y=\frac{\sqrt{x-1} }{4}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B%5Csqrt%7Bx-1%7D%20%7D%7B4%7D)
So if x people were surveyed,
![\frac{7}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B8%7D%20)
people owned a bike and
![\frac{1}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B8%7D%20)
did not.
The difference between them is 72:
![\frac{7}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B8%7D%20)
x-\frac{1}{8} [/tex] =72
so this means that
![\frac{6}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B8%7D%20)
x=72
let's simplify:
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
x=72
and divide by 3:
![\frac{1}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B4%7D%20)
x=24
and mupliply by 4:
x=96
so 96 people were surveyed
Answer:
x = 0
y = -2
Step-by-step explanation:
-5x + y = -2
x = 0
y = -2
-3x + 6y = -12
x = 0
y = -2
4.
4^3 = 64
64X64 = 4096
4^6 = 4096